THE INFLUENCES OF COMPANY CHARACTERISTICS, ENTREPRENEURSHIP BEHAVIOR AND BANK RELATIONSHIP TOWARD SMALL AND MEDIUM ENTERPRISES (SMES) PERFORMANCE - Fatrisia, Alda; Raharja, Edy (Department of Management, Faculty of Economics, Semarang State University, Indonesia, 2015)
This study analyses the influences of company characteristics, entrepreneurship behavior and bank relationship toward Small and Medium Enterprises (SMEs) performance. The object used in this research were 124 owners of SMEs Batik Pekalongan, Central Java. Multiple regression analysis is utilized in this research to examine the hypothesis. The results of the analysis shows that company characteristics, entrepreneurship behavior and bank relationship positively influence the performance of SMEs. The empirical result indicates that the owners of the SMEs of Batik Pekalongan should pay attention on some factors, such as entrepreneurship behavior and bank relationship if they want to increase the performance of their company.